Analisis Faktor Yang Berhubungan Dengan Perilaku Berisiko HIV/AIDS Pada Remaja di Kabupaten Cilacap - Sohimah Sohimah; Sujianti Sujianti (KOLONI, 2024)
The cumulative number of HIV cases reported as of March 2021 was 427,201 (78.7% of the 2020 estimated 90% target for PLWHA of 543,100). The highest percentage of HIV infection was reported in the 25-49 year age group (70.7%), followed by the 20-24 year age group (15.7%), and the ≥ 50 year age group (7.1%\The research carried out was descriptive quantitative research. Descriptive quantitative research uses a correlation approach (correlational research). The research was intended to determine factors related to HIV/AIDS risk behavior among adolescents in Cilacap Regency. Research results: The research results in this study are the factors of knowledge, attitudes and peer support regarding HIV/AIDS risk behavior in adolescents. The majority of adolescent HIV/AIDS risk behavior factors in Cilacap Regency are in the no HIV/AIDS risk category, namely 97%. There is a significant relationship between the level of knowledge and risk behavior in adolescents (p value = 0.012 < α = 0.05). There is a significant relationship between attitude and risk behavior in adolescents (p value = 0.001 < α = 0.05) and there is significant relationship between the role of peers and risky behavior in adolescents (p value = 0.006 < α = 0.05). Suggestions to health workers that education about HIV/AIDS in adolescents be a priority in efforts to prevent behavior at risk of HIV/AIDS transmission.